Hot‐Carrier‐Driven Photodetection: Room‐Temperature High‐Gain Long‐Wavelength Photodetector via Optical–Electrical Controlling of Hot Carriers in Graphene (Advanced Optical Materials 24/2018). Issue 24 (17th December 2018) - Liu, Changlong; Wang, Lin; Chen, Xiaoshuang; Politano, Antonio; Wei, Dacheng; Chen, Gang; Tang, Weiwei; Lu, Wei; Tredicucci, Alessandro
Abstract : Photodetectors exploiting hot electrons have the potential to achieve ultrahigh sensitivity and provide a broadband detection capability. The work by Changlong Liu, Lin Wang, Xiaoshuang Chen and co‐workers (article number 1800836 ) features a novel high‐gain photodetection mechanism aimed at the long‐wavelength photon band via optical–electrical control of intrinsic hot carriers in graphene. A particular potential gradient can be arbitrarily tailored by just controlling the electric field, improving significantly the device activity beyond traditional bandgap engineering.